Chemical study of Mimosa tenuiflora barks. Issue 7 (3rd April 2022) - Amariz, Isabela Araujo e; Pereira, Emanuella Chiara Valença; Alencar Filho, José Marcos Teixeira de; Silva, Jacyara Pereira da; Souza, Nathália Andrezza Carvalho de; de Oliveira, Ana Paula; Rolim, Larissa Araújo; Pereira, Renan Nunes
Abstract: Mimosa tenuiflora (Willd.) Poir., popularly known as "black jurema", is a plant that is predominant in the Caatinga Biome. Drinks used in indigenous rituals use the barks of this plant that are rich in N, N -dimethyltryptamine (DMT), an indolic alkaloid responsible for hallucinogenic activity. The objective of this study was to evaluate the chemical and pharmacognostic characteristics of the Mimosa tenuiflora bark using nuclear magnetic resonance(NMR) analytical techniques and gas chromatography coupled to mass spectrometry(GC-MS) to identify and quantify the DMT present in the extract of Mimosa tenuiflora . The results showed that the plant material is within the recommended standards. Both NMR and GC-MS techniques were able to identify and quantify the DMT with NMR being the best option. In conclusion this study contributes significantly to the standardization of the studied plant material and assists in the use of these data for future development of products from on this forestry species. Graphical Abstract: